The Role of International Labour Organization in Strengthening Global Labor Protection - Haryono Edi Hermawan (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
The International Labour Organization plays a pivotal role in strengthening global labor protection through the establishment of international labor standards, supervision mechanisms, and technical cooperation among member states. This study aims to analyze the contribution of the ILO in promoting workers’ rights, ensuring decent work, and addressing labor violations in the context of globalization. Using a qualitative approach based on literature review, the findings reveal that the ILO has significantly influenced national labor policies through its conventions and recommendations, particularly in areas such as freedom of association, elimination of forced labor, abolition of child labor, and non-discrimination. However, challenges remain in the implementation and enforcement of these standards, especially in developing countries where economic pressures and weak regulatory systems persist. Therefore, strengthening collaboration between international institutions and national governments is essential to enhance compliance and ensure effective labor protection worldwide.